2006
DOI: 10.1140/epja/i2006-10140-7
|View full text |Cite
|
Sign up to set email alerts
|

Deformation change in light iridium nuclei from laser spectroscopy

Abstract: Laser spectroscopy measurements have been performed on neutron-deficient and stable Ir isotopes using the COMPLIS experimental setup installed at ISOLDE-CERN. The radioactive Ir atoms were obtained from successive decays of a mass separated Hg beam deposited onto a carbon substrate after deceleration to 1kV and subsequently laser desorbed. A three-color, two-step resonant scheme was used to selectively ionize the desorbed Ir atoms. The hyperfine structure (HFS) and isotope shift (IS) of the first transition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…Indeed, it was shown that the PTRM calculations [10] successfully described the nuclear spectroscopic data for 187 Au with the assumption that the 9/2 − isomer in 187 Au is the band head of a strongly Coriolis-perturbed rotational band built on the π 1/2 − [541]h 9/2 Nilsson orbital, at a moderate prolate deformation. Similar ground-state bands with anomalous spin sequences were also found, e.g., in 183,185 Au (5/2 − band head) [43,44], 181,183,185 Ir (5/2 − band head) [45][46][47][48], 219 Fr (9/2 − band head) [49], and 221 Fr (5/2 − band head) [50].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, it was shown that the PTRM calculations [10] successfully described the nuclear spectroscopic data for 187 Au with the assumption that the 9/2 − isomer in 187 Au is the band head of a strongly Coriolis-perturbed rotational band built on the π 1/2 − [541]h 9/2 Nilsson orbital, at a moderate prolate deformation. Similar ground-state bands with anomalous spin sequences were also found, e.g., in 183,185 Au (5/2 − band head) [43,44], 181,183,185 Ir (5/2 − band head) [45][46][47][48], 219 Fr (9/2 − band head) [49], and 221 Fr (5/2 − band head) [50].…”
Section: Discussionsupporting
confidence: 71%
“…where g l and g s are the orbital and spin g factors, respectively. The experimental situation when the I π = 9/2 − state becomes the lowest band member corresponds to a very high effective decoupling parameter, a eff dec ≈ +8, whereas its maximal theoretical value is a dec = +5 [48]. This increase provides evidence for a supplementary perturbation coming from the nondiagonal term of the Coriolis interaction [51].…”
Section: Discussionmentioning
confidence: 94%
“…Note that we used expression (8) and not (9) for the field shift, which is consistent with the approach adopted in Ref. [43] where the isotope shifts are calculated according to…”
Section: Using the Line At 351 Nmmentioning
confidence: 92%
“…Another experimental paper dedicated to isotope shifts in neutral iridium was published by Verney et al[43] .They reported IS values for a long chain ofA Ir isotopes A = 193 , 191 , 189 , 187 , 186 m, 186 g, 185 , 184 , 183 , 182 , for the 5 d 7 6 s 2 4 F 9 / 2 → 5 d 7 6 s 6 p 6 F o 11 / 2 transition at 351.5 nm, where the 6 F o 11 / 2 level is the lowest of the J π = (11 / 2) o symmetry. They reported a field shift parameter of F 0 , 351 = −31 .…”
mentioning
confidence: 99%
“…For these elements, states corresponding to a rather large nuclear deformation appear suddenly for a a e-mail: sauvage@ipno.in2p3.fr mass number A < 187 [1][2][3][4][5][6][7], giving rise to shape or deformation change between neighbouring isotopes and/or to coexistence of states having different nuclear shapes or deformations in one nucleus. The most spectacular examples of shape coexistence have been discovered in the 185,186 Hg nuclei where states corresponding to very different deformation parameters, |β| = 0.15 and |β| = 0.25, coexist at low excitation energy [1,2].…”
Section: Introductionmentioning
confidence: 99%